The Efficacy of Different Strengths of Dextrose on Pain Level During Intravenous Cannulation Among Neonates: A Scoping Review (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Introduction: Intravenous (IV) cannulation is a frequently performed and painful procedure in neonates, particularly in the hospital setting. Effective pain management is crucial to mitigate both immediate distress and potential long-term adverse neuro developmental consequences. Methodology: This review synthesizes relevant literature from 2000 to 2024 related to current evidence on the efficacy of various dextrose concentrations (5%, 10%, and 25%) as non-pharmacological interventions for pain reduction during IV cannulation in neonates. A comprehensive literature search was conducted across major medical databases. Results: The review indicates that while 25% dextrose consistently demonstrates a significant analgesic effect for venipuncture and similar minor invasive procedures, direct evidence specifically for IV cannulation at this strength is often extrapolated from venipuncture studies. The efficacy of 10% dextrose for procedural pain is mixed, and 5% dextrose is generally not considered effective for analgesia. Conclusion: While generally safe for oral administration, the review emphasizes the need for more specific research on dextrose's role in IV cannulation pain, distinct from venipuncture, and consistent use of higher effective concentrations.